Design fuzzy neural petri net controller for trajectory tracking control of mobile robot - L. Saleh, Ameer; J. Mohammed, Mohammed; Sabri Kadhim, Ahmed; M. Raadthy, Hana’a; J. Mohammed, Hesham (International Journal of Engineering and Technology, 2018)
In this paper, a Fuzzy Neural Petri Net (FNPN) controller has been designed established on Particle Swarm Optimization (PSO) for controlling the path tracking of Wheeled Mobile Robot (WMR). The path planning controller problem has been solved using two FNPN controllers to get the desired velocity and azimuth. The PSO method has used to detection the optimal values parameters of FNPN controllers. The overall models of wheeled mobile robot for path tracking control created on PSO algorithm are implemented in Simulink-Matlab. Simulation outcomes demonstrate the suggested FNPN controllers is more effectiveness and has good dynamic performance than the conventional methods.Â
Keywords: Mobile Robot; Modeling and Simulation; Trajectory Tracking Technique; PSO Algorithm; FNPN Controller.